Answer:
x = 1
y = 1
(1, 1)
Explanation:
simplify each equation first:
![4x + 6y = 10\\2x + 3y = 5](https://img.qammunity.org/2022/formulas/mathematics/high-school/r81dk3dfz96zo8mwe5q7k0l3diya53syvj.png)
and
![-10x + 2y = -8\\-5x + y = -4](https://img.qammunity.org/2022/formulas/mathematics/high-school/semurtfpe4a2rbpu0lbsdwpwzwna9hdalm.png)
The you would have:
2x + 3y = 5
-5x + y = -4
Multiply both sides of the second equation by 3
![-15x + 3y = -12](https://img.qammunity.org/2022/formulas/mathematics/high-school/5xynya7sfauyq6l7411hj47zv892k1hjw2.png)
Subtract the two equations:
17x = 17
divide both sides by 17
x = 1
substitute this in:
2 + 3y = 5
3y = 3
y = 1